Somatic mutation profiles as molecular classifiers of ulcerative colitis‐associated colorectal cancer. Issue 12 (13th February 2021) - Mäki‐Nevala, Satu; Ukwattage, Sanjeevi; Olkinuora, Alisa; Almusa, Henrikki; Ahtiainen, Maarit; Ristimäki, Ari; Seppälä, Toni; Lepistö, Anna; Mecklin, Jukka‐Pekka; Peltomäki, Päivi
Abstract: Ulcerative colitis increases colorectal cancer risk by mechanisms that remain incompletely understood. We approached this question by determining the genetic and epigenetic profiles of colitis‐associated colorectal carcinomas (CA‐CRC). The findings were compared to Lynch syndrome (LS), a different form of cancer predisposition that shares the importance of immunological factors in tumorigenesis. CA‐CRCs (n = 27) were investigated for microsatellite instability, CpG island methylator phenotype and somatic mutations of 999 cancer‐relevant genes ("Pan‐cancer" panel). A subpanel of "Pan‐cancer" design (578 genes) was used for LS colorectal tumors (n = 28). Mutational loads and signatures stratified CA‐CRCs into three subgroups: hypermutated microsatellite‐unstable (Group 1, n = 1), hypermutated microsatellite‐stable (Group 2, n = 9) and nonhypermutated microsatellite‐stable (Group 3, n = 17). The Group 1 tumor was the only one with MLH1 promoter hypermethylation and exhibited the mismatch repair deficiency‐associated Signatures 21 and 15. Signatures 30 and 32 characterized Group 2, whereas no prominent single signature existed in Group 3. TP53, the most common mutational target in CA‐CRC (16/27, 59%), was similarly affected in Groups 2 and 3, but DNA repair genes and Wnt signaling genes were mutated significantly more often in Group 2. In LS tumors, the degree of hypermutability exceeded that of the hypermutated CA‐CRC Groups 1 and 2, and somatic mutational profiles and signatures were different. In conclusion, Groups 1 (4%) and 3 (63%) comply with published studies, whereas Group 2 (33%) is novel. The existence of molecularly distinct subgroups within CA‐CRC may guide clinical management, such as therapy options. Abstract : What's new? Ulcerative colitis‐associated colorectal carcinoma (CA‐CRC) is a complex disease involving inflammation‐associated tumorigenesis and genetic mutation. Despite extensive knowledge of germline defects linked to CA‐CRC, however, molecular pathogenesis of the disease remains poorly defined. In this study, using tumor profiling, the authors describe three genetic and epigenetic CA‐CRC subgroups, two of which are previously known and one that is novel. The novel subgroup consisted of hypermutated microsatellite‐stable tumors, which displayed distinct mutational signatures compared to the remaining CA‐CRC subgroups and Lynch syndrome tumors, suggesting pathophysiologic differences. The existence of molecular subgroups within CA‐CRCs may inform treatment decisions.